The Conceptual Mind : New Directions in the Study of Concepts - Laurence, Stephen; Margolis, Eric, 1968- (Book collections on Project MUSE., 2015)
"The study of concepts has advanced dramatically in recent years, with exciting new findings and theoretical developments. Core concepts have been investigated in greater depth and new lines of inquiry have blossomed, with researchers from an ever broader range of disciplines making important contributions. In this volume, leading philosophers and cognitive scientists offer original essays that present the state-of-the-art in the study of concepts. These essays, all commissioned for this book, do not merely present the usual surveys and overviews; rather, they offer the latest work on concepts by a diverse group of theorists as well as discussions of the ideas that should guide research over the next decade. The book is an essential companion volume to the earlier Concepts: Core Readings, the definitive source for classic texts on the nature of concepts. The essays cover concepts as they relate to animal cognition, the brain, evolution, perception, and language, concepts across cultures, concept acquisition and conceptual change, concepts and normativity, concepts in context, and conceptual individuation"--MIT CogNet.